Acúmulo de matéria seca e de nutrientes em cultivares de bananeira irrigada - Hoffmann, Ricardo Bezerra (2008)
The evaluation of accumulation and distribution of dry matter and nutrients in the vegetative and reproductive parts of banana plant provide important data for the estimation of the demand of nutrients by the plant. However, as larger the amount of part or organs that compose the plant, larger will be the amount of chemical analyses and therefore the costs for accomplishing the research work. It is possible that the chemical analyses of only one composed sample of dry matter from different part of the plant would be sufficient for estimating the mean nutrient contents in the plant, considering that in the composition of the composed sample, the amount of dry matter from each part of the plant evaluated is in agreement with the proportion that such part represents in relation to the whole plant. The objectives of that work were: a) to evaluate the accumulation of dry matter and nutrients in six irrigated banana plant cultivars; b) to evaluate the feasibility of the use composed sample of vegetable tissue for evaluating the content of macronutrients in several organs from the banana plant. It was sampled plants from the cultivars Grande Naine, Pacovan, Pacovan-Apodi, Prata Anã, Terrinha and Gross Michel, from a commercial production area of irrigated banana plant from the Frutacor Ltda Farm. Those cultivars were cropped in double rows, being 1,666 plants per ha. At the harvest time, it was selected four banana plant-bunches from each cultivars for sampling. The "mother-plant" was divided in rhizome, pseudostem, petiole, leaf lamina, stalk, and fruits, and those part were weighted for fresh matter determination. Following, it was collected a sample of approximately 700 g from each part of the plant for dry matter determination. Those samples were washed, put inside paper bags, and sent to the vegetable tissue analysis laboratory, where were dried in oven until the constant weight be reached, for the determination of N, P, K, Ca, Mg, S, B, Cu, Zn, Fe, and Mn contents. For the evaluation of the feasibility of the use of composed samples of vegetable tissue, it was sampled four families of irrigated banana plant cv. Gross Michel that was separated into "mother-plant" and "daughter-plant". The "mother-plant" was divided into rhizome, pseudostem, petiole, leaf lamina, stalk, and fruits, and to the "daughter-plant" into rhizome, pseudostem, petiole and leaf lamina. Following, it was collected samples from those parts for dry matter and N, P, K, Ca, Mg, and S contents determination. From the dry matter from each part of the plant, it was removed sub-samples for preparation of the composed samples. The cultivars that extracted the largest amount of nutrients from the soil were, in general manner, those that accumulated the highest amounts of dry matter. Potassium (K) and N were the macronutrients more absorbed and exported by the cultivars in study, followed by S, Ca, Mg, and P. For all cultivars there was larger accumulation of Mn and Fe in the plant, being the two micronutrients more exported by the banana plant by harvest time. Cu was the micronutrient accumulated in lower amounts by the six cultivars, with exception of the Gross Michel cultivar that accumulated and exported more Cu than Zn. The results for the use of composed samples indicate that the interval of the mean error between approaches for each nutrient was not large. Therefore, the chemical analysis of only one composed sample from different smaller parts of banana plant is sufficient for estimating the mean contents of N, P, K, Ca, Mg, and S in a larger part of the plant or from the whole plant, considering that in the composition of that composed sample the amount of dry matter from each smaller part is in agreement with a proportion that such part represents in relation to the larger part or to the whole plant.